PENYELIDIKAN KASUS ORGANISASI TERORISME DAN METODENYA (STUDI KASUS: AKTIVITAS SEL JAMAAH ISLAMIAH DI INDONESIA PERIODE 2001-2012) - Andrea Abdul Rahman; Retta Andriani; Yusran Yusran; Pudiastuti Citra Adi (Transnasional, 2018)
October 12th, 2002 terrorism attack in Bali became the starting point of counter-terrorism movement, especially against those who are strongly indicated as being affiliated with Al-Qaeda, which is Jemaah Islamiyah (JI). The 2002 Bali bombing, followed by the 2005 Bali bombing, has put Indonesia on a reality that she has not only become the bases of terrorism movement, but also the victim of such movement. In order to comprehensively stop the terror activities and terrorist, the Government of Indonesia prefers the rule of law, in which the legal officials—including the police force and prosecution institution—stand in the front line. Therefore, this writing aims to study the policies and efforts in countering terrorism at the ‘action’ phase involving legal instruments. Then, this article also aims to analyze on how ‘disengagement’ method and ‘enhanced criminal justice model’ are able to overcome terrorism acts. The results show that since the period of President Soekarno’s administration until President Yudhono’s administration, the effort has evoluted. Indonesia has implemented the hard—military—approach which is lasted until 2003. Under President Yudhoyono, there’s new formulation of the hard approach which prefers non-military legal upholding which is Enhance Criminal Justice Model. The government has sets the police force—Densus 1988 AT—as the front line.